2008
DOI: 10.1055/s-0028-1088315
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antiparasitic Activity of Oleanolic Acid and its Glycosides isolated from Marigold (Calendula officinalis)

Abstract: The antibacterial and antiparasitic activities of free oleanolic acid and its glucosides and glucuronides isolated from marigold (Calendula officinalis) were investigated. The MIC of oleanolic acid and the effect on bacterial growth were estimated by A600 measurements. Oleanolic acid's influence on bacterial survival and the ability to induce autolysis were measured by counting the number of cfu. Cell morphology and the presence of endospores were observed under electron and light microscopy, respectively. Ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 17 publications
2
46
0
1
Order By: Relevance
“…The previously described results of Szakiel and coworkers [31] demonstrated that OA not only acted as a potent inhibitor of the growth and survival of several species but it also influenced bacterial shape. E. coli cells appeared several-fold longer, in contrast B. megaterium cells became shorter after an overnight incubation with OA at a concentration of 0.7 x MIC.…”
Section: Cellular Targets and Functions Affected By Oa Ua And Their mentioning
confidence: 83%
See 3 more Smart Citations
“…The previously described results of Szakiel and coworkers [31] demonstrated that OA not only acted as a potent inhibitor of the growth and survival of several species but it also influenced bacterial shape. E. coli cells appeared several-fold longer, in contrast B. megaterium cells became shorter after an overnight incubation with OA at a concentration of 0.7 x MIC.…”
Section: Cellular Targets and Functions Affected By Oa Ua And Their mentioning
confidence: 83%
“…All other species studied by Szakiel and Escherichia coli were moderately susceptible to OA [31] (Table 1). Gu and coworkers evaluated the antitubercular activity of OA extracted from Quinchamalium majus (Santalaceae), using the microplate alarm blue assay (MABA) system [32] and discussed structure-activity relationships.…”
Section: Antibacterial Activity Of Oa and Its Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Flora of Syria, this genus is represented by 8 species [1]. Previous studies demonstrated therapeutic potentialities of Calendula officinalis L. such as anti-inflammatory activity [2][3][4][5], immunomodulatory [6][7], Hepatoprotective [8], wound-healing [9], antioxidant [10][11][12], antibacterial and antiparasitic activity [13][14][15][16]. The essential oil from C. officinalis has been also investigated [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%